تمثّلات قيم المواطنة لدى تلاميذ المرحلة الابتدائية في ظل إصلاحات الجيل الثاني - عيشون سامية; قاسمي صونيا (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2022)
لا شك أن العملية التعليمية هي محاولة إعداد برامج دراسية من أجل توجيه التلميذ وتنمية سلوكه، لتتماشى مع البيئة الاجتماعية من أجل رفع المستوى التعليمي. وجاء التركيز في هذه الدراسة على إصلاح المنظومة التربوية في المدرسة الجزائرية، حيث تم اعتماد اصلاحات الجيل الثاني من أجل معالجة قصور المناهج السابقة، وتكمن أهميتها في التكفل بالبعد القيمي والأخلاقي في المناهج، والهدف من ذلك تكوين تمثّلات إيجابية لدى تلاميذ المرحلة الابتدائية حول قيم المواطنة التي تشمل أبعاد الهوية الوطنية والانتماء الوطني واحترام رموز السيادة الوطنية. The educational process, with no doubt, is an attempt of preforming study programs for the pupil orientation and the development of his behaviour according to the social environment. It aims to improve his educational level. This study focuses on reforming the educational system in the Algerian school. The 2nd generation reforms have been adopted for improving the previous curricula discrepancy. Their importance lies in ensuring the value and the ethical dimension in the curricula for forming positive representations with the pupils at the primary stage about the citizenship values, which include the national identity dimensions, the national belonging, and respecting the national sovereignty symbols.